2015
DOI: 10.1089/end.2014.0332
|View full text |Cite
|
Sign up to set email alerts
|

Tools to Improve the Accuracy of Kidney Stone Sizing with Ultrasound

Abstract: Stone size is consistently overestimated with US. Overestimation increased with increasing depth and gain using the commercial machine. Overestimation was reduced and did not vary with depth, using the software-based US device. The computerized stone-sizing program shows the potential to reduce overestimation by implementing a grayscale intensity threshold for defining the stone size. More work is needed to standardize the approach, but if successful, such an approach could significantly improve stone-sizing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 15 publications
1
34
0
1
Order By: Relevance
“…5,7,10 The average overestimation reported previously and here is on the order of 1.5 to 2.0 mm. Conventional ray line imaging is more accurate in measuring stone size than spatial compound imaging, but when measuring the stone directly the most accurate results were with harmonic imaging.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…5,7,10 The average overestimation reported previously and here is on the order of 1.5 to 2.0 mm. Conventional ray line imaging is more accurate in measuring stone size than spatial compound imaging, but when measuring the stone directly the most accurate results were with harmonic imaging.…”
Section: Discussionsupporting
confidence: 49%
“…Recent literature has shown that system settings and US imaging modality can affect the appearance of the hyperechoic boundaries and, thus, the measured stone size. 7 However, the edges of the acoustic shadow do not undergo the same distortion as the hyperechoic stone. In this study we investigated the acoustic shadow width as an alternative measure of stone size.…”
mentioning
confidence: 99%
“…Taking this research even further, our group is working on a stone-specific mode for ultrasonography termed ‘S-mode’ to harness the inherent differences between stones and their surrounding tissues 42,44 . Ultrasonographic greyscale imaging is currently optimized for visualization and differentiation of soft tissues.…”
Section: Ultrasonographymentioning
confidence: 99%
“…7 This includes reducing the use of smoothing algorithms and the compression of high signal-intensity regions to improve visualization and sharpen contrast at the edge of stones and in the posterior shadow. 8,9 These techniques have been incorporated into an US imaging modality, coined the stone-specific mode, or S-mode.…”
Section: Introductionmentioning
confidence: 99%